A Critical Review on Manyasthambha and its Management, Including Pathya and Apathya in Ayurveda (AYUSHDHARA, 2025)
In Today’s era, due to the lack of exercise, sedentary lifestyle and stress, 70% of general population is affected with neck pain during their life. Manyasthambha is one such disease which leads to stiffness or rigidity in the neck associated with pain and mobility of neck is impaired. Manyasthambha is one of the Vataja Nanatmaja Vyadhi, as well as Urdwajatrugata Vikara. In Manyasthambha, the Vata gets provoked by Kaphavruta, in result Stambha and Ruk. In modern science, it is compared to cervical spondylosis which is a progressive degenerative change that affects the cervical spine.